BLITZ-HF study: a nationwide initiative to assess and improve guidelines recommendations adherence in cardiology centers managing patients with acute and chronic heart failure. (14th October 2021) - Orso, F; Di Lenarda, A; Oliva, F; Aspromonte, N; Greco, C; Di Tano, G; Lucci, D; Maggioni, A.P; Mortara, A; Pagnoni, N; Pajes, G; Uguccioni, M; et al.
Abstract: Background: Physicians adherence to heart failure (HF) guidelines is generally sub-optimal with consequent negative prognostic implications. Strategies to improve adherence to guideline recommendations are strongly needed. Aims: To assess and improve adherence of Italian cardiology sites to guidelines recommendations on performance indicators in patients with acute (AHF) and chronic heart failure (CHF). Methods: BLITZ-HF was a prospective study based on a web based recording system used during two enrollment periods (phase 1 and 3), interspersed by face-to-face macro-regional benchmark analysis and educational meetings (phase 2). Both management (creatinine and echocardiographic evaluations or discharge follow-up planning) and treatment (according to ejection fraction categories, focusing on guidelines directed medical treatments - GDMTs) performance indicators were considered for patients in both settings. Results: Overall, 7218 patients with acute and chronic HF were enrolled at 106 sites. During the enrollment phases, 3920 and 3298 patients were included respectively, 84% with CHF and 16% with AHF in phase 1, 74% with CHF and 26% with AHF in phase 3. In Figure 1 we report adherence to management and treatment indicators in the two enrollment phases. Among AHF patients improvement was obtained in two of seven indicators. A significant rise in echocardiographic evaluation was observed, while discharge schedule of a cardiology ambulatory evaluation within four weeks was overall poor (less than 50%) and did not improve in the 3 phase. Overall GDMTs prescription rate in HFrEF was good and we observed a nominal increase in betablockers prescription rate in Phase 3. Among CHF patients with HFpEF and HFmrEF we observed a performance increase in two of three indicators: creatinine end echocardiographic evaluations, while oral anticoagulation in atrial fibrillation remained stably high. Performance measures in CHF HFrEF patients improved in six of nine indicators although significantly only in two. Prescription rate of GDMTs was good already in phase 1 and a significant increase in ACE-I/ARB or ARNI prescription was reported, with a nominal increase in the use of one of these three drugs in combination with MRAs and a BB. Conclusions: A structured multifaceted educational intervention can improve adherence to HF guidelines on several indicators in a context of an already elevated level of adherence to guideline recommendations. Extension of this approach to other non-cardiology health professional settings, in which patients with HF are generally managed, should be considered. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The study was funded by Heart Care Foundation with a partial unrestricted support from Abbott, Daiichi Sankyo, Medtronic, Servier, Vifor.